The effect of using some help in learning the accuracy of performance and achievement of some basic tennis skills - Jabbar Abbas, Ammar (International Journal of Psychosocial Rehabilitation, 2020)
The aim of the research is to detect the effect of using Some aids in acquiring the art of performance and accuracy of achievement For a tennis serve kick. And use the experimental method Due to its relevance to the nature of the problem, the research sample consisted of (30) students From the students of the College of Physical Education and Sports Sciences / University of Diyala, they were deliberately selected from the students of the third stage of the morning study for the academic year 4/3/2022 until 25/4/2022, divided into three experimental groups of (10) students for each group, and they were parity in Variables (age, height, weight) as well as a number of physical and kinetic components. And each of the three groups implemented its own program according to the following methods: The first educational program (the method of implementing practical exercises on the wall). The second educational program (method of implementing applied exercises in the regular playground). The third educational program, the integration (method of implementing practical exercises on the wall and in the regular playground), and took to implement Software educational ten weeks And in reality three units educational in the week the one, In a time of (90) minutes for every lonliness educational, and the researcher concluded that the use of the first educational program (using the method of implementing applied exercises on the wall) is effective in developing the art of performance and the accuracy of achievement of the transmitter skill when compared to their colleagues in the second and third programs.